Theologies of human agency: counterbalancing divine in/activity in the Megilloth - Strollo, Megan Fullerton (Lexington Books/Fortress Academic, 2022)
Theologies of Human Agency: Counterbalancing Divine In/Activity in the Megilloth demonstrates the diversity of theological thought implicit in the Hebrew Bible through an examination of the books of Ruth, Song of Songs, Ecclesiastes, Lamentations, and Esther. These postexilic works portray human agency as a vital counterpoint to divine skepticism.